Transcriptional Activation of Gstp1 by MEK/ERK Signaling Confers Chemo-Resistance to Cisplatin in Lung Cancer Stem Cells - Li, Jingyuan; Ye, Ting; Liu, Yongli; Kong, Liangsheng; Sun, Zhiwei; Liu, Doudou; Wang, Jianyu; Xing, H. Rosie (Frontiers in Oncology, 2019)
Lung cancer management remains challenge due to its asymptomatic and late presentation when it is metastatic. Clinical response to the first-line platinum-based chemotherapy in patients with advanced lung cancer is disappointing due to the development of chemoresistance. Chemoresistance is a complex phenomenon. Mechanistic understanding using experimental models have yielded limited clinically understanding for overcoming resistance. While the role of lung CSCs in conferring multidrug resistance has been postulated, experimental evidence remains associative and lacks in depth mechanistic inquisition. In the present study, using mouse and human lung adenocarcinoma cell lines and their respective paired CSC derivative cell lines that we generated, we identified cancer stem cell component of lung adenocarcinoma is the source that confers multidrug resistance phenotype. Mechanistically, Gstp1 confers cisplatin resistance in mouse and human lung CSC models, both in vitro and in vivo. Further, transcriptional activation of Gstp1 expression by MEK/ERK signaling underlies cisplatin resistance in lung CSC cells. Moreover, we show that GSTP1 expression is a poor diagnostic and prognostic marker for human lung adenocarcinoma thus is of high clinical relevance. Taken together, we have provided mechanistic understanding of the lung CSC in mediating chemoresistance.